Geospatial and Temporal Analysis of a 20‐Year Record of Landsat‐Based Water Clarity in Minnesota's 10, 000 Lakes1. (20th November 2013) - Olmanson, Leif G.; Brezonik, Patrick L.; Bauer, Marvin E.
Abstract A large 20‐year database on water clarity for all Minnesota lakes ≥8 ha was analyzed statistically for spatial distributions, temporal trends, and relationships with in‐lake and watershed factors that potentially affect lake clarity. The database includes Landsat‐based water clarity estimates expressed in terms of Secchi depth (SDLandsat), an integrative measure of water quality, for more than 10, 500 lakes for time periods centered around 1985, 1990, 1995, 2000, and 2005. Minnesota lake clarity is lower (more turbid) in the south and southwest and clearer in the north and northeast; this pattern is evident at the levels of individual lakes and ecoregions. Temporal trends in clarity were detected in ~11% of the lakes: 4.6% had improving clarity and 6.2% had decreasing clarity. Ecoregions in southern and western Minnesota, where agriculture is the predominant land use, had higher percentages of lakes with decreasing clarity than the rest of the state, and small and shallow lakes had higher percentages of decreasing clarity trends than large and deep lakes. The mean SDLandsat statewide remained stable from 1985 to 2005 but decreased in ecoregions dominated by agricultural land use. Deep lakes had higher clarity than shallow lakes statewide and for lakes grouped by land cover. SDLandsat decreased as the percentage of agriculture and/or urban area increased at county and catchment levels and it increased with increasing forested land.